Application of the slope‐ratio growth assay technique to estimate tryptophan availability in soybean meal fed to young rats. (5th August 2019) - Sato, Hiroyuki; Miura, Makoto; Fujieda, Takeshi; Toyomizu, Masaaki
Abstract: The slope‐ratio assay for rat was used to determine whether tryptophan (Trp) availability in soybean meal (SBM) is affected by the presence of other amino acids (AAs). In a preliminary study, rats were fed graded levels of Trp‐supplemented diets to establish the Trp concentration range over which the weight gain response was linear. This range was found to be from 0.04% to 0.12% Trp. Subsequently, rats were fed basal (0.045% Trp) or Trp‐supplemented diets from three different sources:l ‐Trp alone, SBM, orl ‐Trp mixed with other AAs to reflect AA levels in the test SBM (AA‐mix). Weight gain in rats increased linearly with supplemental Trp intake ( p < .05) for all Trp sources. Compared to the slope achieved withl ‐Trp alone, the estimated availability of Trp in SBM was 84.4%, while for the AA‐mix it was 93.4%. It is evident that the 6.6% reduction inl ‐Trp availability in AA‐mix is due to metabolic costs derived from excess levels of other AAs beside Trp, given that the absorption of crystallinel ‐Trp in the small intestine is 100%. In conclusion, the Trp availability of SBM was estimated to be around 90.4% (i.e., 84.4/93.4 × 100) after correcting for the effects of the other AAs in SBM.